Silicon(lithiated)–sulfur full cells with porous silicon anode shielded by Nafion against polysulfides to achieve high capacity and energy density. (January 2016) - Shen, Chenfei; Ge, Mingyuan; Zhang, Anyi; Fang, Xin; Liu, Yihang; Rong, Jiepeng; Zhou, Chongwu
Abstract: Lithium-ion batteries have attracted great attention as one of the most versatile electrochemical energy storage devices. However, to meet the ever-growing energy needs for wide applications, further improvements on energy density of batteries are expected, which requires the development of innovative high-energy electrode materials. Silicon (Si) and sulfur (S) are two promising candidates and have been studied intensively as anode and cathode materials in lithium-ion batteries. Nevertheless, the excellent performance achieved with Li–Si and Li–S half cells usually does not easily translate to high-performance Si–S full cell. Here, we will discuss the challenges in the Si–S full cell integration, and a failure mechanism of Si–S full cell is proposed, which is due to the spontaneous reaction between Si (and lithiated Si) and polysulfides. On this basis, we report one prototype of Si-S full cells using lithiated Nafion-coated porous Si as anode and sulfur as cathode, and our study on the functionality of Nafion in shielding Si from reaction with polysulfides. With optimized mass ratio between sulfur and silicon, the full cell yields specific capacity of 330 mA h/g and energy density of 590 W h/kg after 100 cycles based on the total mass of sulfur and silicon. The achieved energy density is more than 2 times higher than commercially available lithium-ion batteries. The investigation of issues in Si–S full cell research and the proposed full cell prototype will shed light on the development of next-generation lithium-ion batteries. Graphical abstract: Highlights: We report Si–S full cells with lithiated Nafion-coated porous Si as anode. We report that spontaneous Li x Si–Li2 S y reaction leads to failure of Si-S full cell. Nafion coating on Si anode improves the Si–S full cell performance. High specific capacity of Si–S full cell is achieved by optimizing S/Si mass ratio. The full cell yields capacity of 330 mA h/g and energy density of 590 W h/kg.